Deregulated High Affinity Copper Transport Alters Iron Homeostasis in Arabidopsis - Perea-García, Ana; Andrés-Bordería, Amparo; Vera-Sirera, Francisco; Pérez-Amador, Miguel Angel; Puig, Sergi; Peñarrubia, Lola (Frontiers in Plant Science, 2020)
The present work describes the effects on iron homeostasis when copper transport was deregulated in Arabidopsis thaliana by overexpressing high affinity copper transporters COPT1 and COPT3 (COPTOE). A genome-wide analysis conducted on COPT1OE plants, highlighted that iron homeostasis gene expression was affected under both copper deficiency and excess. Among the altered genes were those encoding the iron uptake machinery and their transcriptional regulators. Subsequently, COPTOE seedlings contained less iron and were more sensitive than controls to iron deficiency. The deregulation of copper-(I) uptake hindered the transcriptional activation of the subgroup Ib of basic helix-loop-helix (bHLH-Ib) factors under copper deficiency. Oppositely, copper excess inhibited the expression of the master regulator FIT but activated bHLH-Ib expression in COPTOE plants, in both cases leading to the lack of an adequate iron uptake response. As copper increased in the media, iron (-III) was accumulated in roots, accounting for a defective iron mobilization to the aerial parts, and the ratio iron (III)/iron (II) is effect was increasexacerbated in COPTOE plants. Thus, iron (-III) overloading in COPTOE roots inhibited local iron deficiency responses, aimed to metal uptake from soil, leading to a general lower iron content in the COPTOE seedlings. These results emphasized the importance of appropriate spatiotemporal copper uptake for iron homeostasis under non-optimal copper supply. The understanding of the role of copper uptake in iron metabolism could be applied for increasing crops resistance to iron deficiency.